Hilirisation Agricultural Zakat as a Basis for Increasing Community Income - Razali, Ramadhan; Rahmawati, Rahmawati (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2024)
The downstreaming of zakat in the agricultural sector (agricultural zakat) is one of the strategic efforts to increase people's income, especially farmers, while encouraging sharia-based economic independence. Agricultural zakat has great potential in supporting the optimal management of agricultural products through the appropriate distribution of zakat, but its implementation still faces various challenges such as low understanding of farmers, ineffective distribution, and lack of innovation in the management of zakat results. This study aims to analyse the downstream potential of agricultural zakat as a basis for increasing community income, especially among small and medium farmers. This study also evaluates the effectiveness of agricultural zakat management in encouraging farmers' productivity and welfare. Data was collected through mixed-method which includes in-depth interviews, field observations, and secondary data analysis from reports of zakat institutions and related institutions. The results show that the downstreaming of agricultural zakat can increase community income through various empowerment programmes, such as the provision of farming capital, training on modern cultivation techniques, and opening market access for agricultural products. In addition, the synergy between zakat institutions, government, and local communities is a key factor in the success of this programme. In conclusion, the downstreaming of agricultural zakat has great potential to support sharia-based community economic empowerment. However, a stronger regulatory framework and cross-sector collaboration are needed for optimal and sustainable implementation.